Static behavior of partially earth-anchored cable-stayed bridge of different side-to-main span ratios: super-long span system with crossing cables. (October 2021) - Alsayed, Motasem; Lin, Lan; Hassan, Jassim
Abstract: This article presents a study to evaluate the structural response of a cable-stayed bridge under a novel system, partially earth-anchored system with crossing cables at the main span. Six side-to-main span ratios, ranging from 0.24 to 0.39 in increments of 0.03, are tested for different bridge response parameters for both the superstructure and substructure. The loads considered in the analysis are the dead load and traffic load. Three-dimensional finite element models of the bridge are developed using structural analysis software SAP2000 and are validated based on the data available in the literature. From this study, it is found that the side-to-main span ratios have a significant effect on girder axial force and anchorage forces while having a very minor effect on cable axial forces. The results also show that the ratio does not affect the bending moment of the main span, but that when a small ratio is considered particular attention needs to be paid to the pier farther from the pylon to avoid uplifting. Deck vibration and longitudinal movement, as well as pylon longitudinal displacement, are not to be an issue for this super-long bridge.